2019
DOI: 10.1002/1878-0261.12504
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor signals regulate transforming growth factor‐β‐induced endothelial‐to‐myofibroblast transition of tumor endothelial cells via Elk1

Abstract: The tumor microenvironment contains various components, including cancer cells, tumor vessels, and cancer‐associated fibroblasts, the latter of which are comprised of tumor‐promoting myofibroblasts and tumor‐suppressing fibroblasts. Multiple lines of evidence indicate that transforming growth factor‐β ( TGF ‐β) induces the formation of myofibroblasts and other types of mesenchymal (non‐myofibroblastic) cells from endothelial cells. Recent reports show that fibroblast growth factor 2 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 53 publications
3
36
0
1
Order By: Relevance
“…Recently, FGF2 was shown to not only inhibit TGF-β-induced endothelial-to-myofibroblast transition (End-MyoT) mediated via the transcription factor ELK1, but also promoted the formation of active fibroblastic cells with migratory and proliferative characteristics. This revealed the opposing and cooperative action between FGF and TGF-β signaling during the modulation of different mesenchymal cell phenotypes (Akatsu et al, 2019). In mouse embryos with ECs deficient in β-catenin, the cardiac cushion had fewer cells, suggesting that β-catenin in ECs is needed for efficient EndMT and invasion of the mesenchymal cells into the cardiac jelly to form cardiac septa and valves.…”
Section: Interplay With Other Signaling Pathways That Mediate or Regumentioning
confidence: 99%
“…Recently, FGF2 was shown to not only inhibit TGF-β-induced endothelial-to-myofibroblast transition (End-MyoT) mediated via the transcription factor ELK1, but also promoted the formation of active fibroblastic cells with migratory and proliferative characteristics. This revealed the opposing and cooperative action between FGF and TGF-β signaling during the modulation of different mesenchymal cell phenotypes (Akatsu et al, 2019). In mouse embryos with ECs deficient in β-catenin, the cardiac cushion had fewer cells, suggesting that β-catenin in ECs is needed for efficient EndMT and invasion of the mesenchymal cells into the cardiac jelly to form cardiac septa and valves.…”
Section: Interplay With Other Signaling Pathways That Mediate or Regumentioning
confidence: 99%
“…Conversely, recent studies demonstrated that ECs resist specific conversion to alpha-SMA+ myofibroblast-like cells when the cells are challenged with TGFβ through secretion of bFGF [83]. TGFβ and bFGF could oppose and cooperate with each other during EndMT via Elk1 [84]. These data suggest that EndMT is another mechanism producing TEC heterogeneity.…”
Section: Heterogeneity Of Tecsmentioning
confidence: 99%
“…2 We recently reported that transforming growth factor-β (TGF-β) induced the transition from tumor ECs (TECs) to α-smooth muscle actin (αSMA)-positive mesenchymal cells (myofibroblasts), which induced tumor formation more potently than αSMA-negative TEC-derived mesenchymal cells. 5 In addition to formation of CAFs during EndMT, loss of the endothelial barrier of the tumor vasculature can be observed, suggesting an important role of EndMT in facilitating metastatic dissemination. Thus, effective targeting of EndMT is likely to result in the development of novel anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%